KRITIK SOSIAL DALAM NOVEL BALADA GATHAK GATHUK KARYA SUJIWO TEJO KAJIAN TEORI SOSIAL KRITIS JURGEN HUBERMAS - AFSA NASIH AL-AMIN, MUHAMMAD (BAPALA, 2018)
Abstract This research is very much based on the incident that happened in social environment some of last time. Sujiwo Tejo formed a criticism in the form of a novel entitled Balada Gathak-Gathuk. The novel describes the various forms of criticism in terms of political criticism, legal criticism, social criticism, health criticism, educational criticism, and economic criticism. This study uses a critical social theory study from Jurgen Hubermas with various aspects. This research uses Jurgen Hubermass theory which explains social criticism is krtiik which is done in the activity bersoial and can be done by anyone. There are three core concepts contained in Jurgen Hubermass critical social theories: stratergistic, communicative and real-life actions. Of these three core aspects can enter into various criticisms from different fields such as, criticism in the field of politics, criticism in the social field, criticism in the field of law, critics in the field of health, krtiik in the field of education, and critics in the field of economics. Penelitian ini menggunakan metode dekriptif kualitatif kualitatif dengan menggunakan pendekatan sosiologi sastra yang lebih melihat sangkut paut kehidupan dan masalah yang ada di dalam masyarakat. Sumber data penelitian ini adalah Novel Balada Gathak Gathuk karya Sujiwo Tejo, yang terdiri atas 272 halaman. Dalam penelitian ini dapat ditemukan lebih kurang 40 bukti terbagi dari 11 bukti kritik sosial dalam bidang politik, 12 kritik sosial dalam bidang sosial, 3 bukti kritik sosial dalam bidang hukum, 4 bukti kritik sosial dalam bidang pendidikan, dan 4 bukti kritik sosial dalam bidang kesehatan dan 3 bukti kritik sosial dalam bidang ekonomi. Kata Kunci: Kritik sosial, Jurgen Hubermas, dan berbagai jenis kritik. Abstract An This research is based on the incident that occurred in the social environment some time ago. Sujiwo Tejo formed a criticism in the novel that was titled Balada Gathak-Gathuk. The novel describes the various forms of criticism in terms of political criticism, legal criticism, social criticism, health criticism, educational criticism, and economic criticism. This study uses a critical social theory study with various aspects from Jurgen Hubermas. His research uses Jurgen Hubermass theory that explained social criticism. A criticism can be done in social activities and can be done by anyone. There were 3 core concepts contained in the critical social theory of Jurgen Hubermas, which is strategic action, communicative action and real life. The three core aspects could enter into various criticism from various fields such as, criticism in the field of politics, criticism in the social field, criticism in the field of law, critics in the field of health, criticism in the field of education, and criticism in the field of economics. This research uses descriptive qualitative method by using approach of sociology literature which is adopt relation of life and problem exist in society. The data source of this research is Novel Balada Gathak Gathuk by Sujiwo Tejo, which consists of 272 pages. In this research can be found in more than 40 publications of social criticism, 12 social criticisms in the social field, 3 social evidences in the field of law, 4 social criticisms in the field of health and 3 social evidences of economic criticism. Keywords: Social criticism, Jurgen Hubermas, various types of criticism.